Pengaruh komunikasi organisasi dan motivasi terhadap kinerja freelance di Jagoketik.com - Nuniek Dewi Pramanik (Penerbit Goodwood, 2020)
Purpose: This paper aimed to examine the impact of organizational communication and motivation on the freelancer’s performance of Jagoketik.com. This research needed to be discussed because the increase in employee performance could be influenced by organizational communication and motivation. Research Methodology: The population in this study was all freelancers at Jagoketik.com, with a total of 31 employees. The research design used was quantitative research, using a descriptive approach with an emphasis on theory testing through the measurement of research variables through the distribution of research questionnaires. The sampling technique used was nonprobability sampling through saturated sampling (census). The analysis technique was done through multiple linear regression with SPSS 21.0 software. Limitations: Constraints of respondents asked for data virtually and limited scope of the research were two main limitations of this study. Result: The results of this study show that organizational communication and motivation variables have a significant and positive effect on the performance of freelancer both simultaneously and partially. Contributions: If Jagoketik.com wants to improve the employee’s performance, they can optimize organizational communication and motivation indicators. Keywords: Organizational communication, Motivation, Employee performance, Freelancer, Jagoketik.com